HUBUNGAN PENYULUHAN KESEHATAN TENTANG PENCEGAHAN DIARE PADA BALITA DENGAN SIKAP IBU DALAM PENCEGAHAN DIARE PADA BALITA - Cahyono, Aris Dwi (Jurnal AKP, 2012)
Diarrheal disease in Indonesia is a health problem and attacking all ages including children under five. Required health education that is easily understood in terms of adding knowledge and attitude of a good mother in prevention. The research objective was to prove the relationship of health education on the prevention of diarrhea in infants with maternal attitudes in the prevention of diarrhea in infants in health center Kandangan 2010.The study design was cross sectional. The population is mothers who have children under five suffer from diarrhea and had as many as 42. Sample of 40 mothers and purposive sampling techniques sampling. Data collected with the questioners and presented in the form of diagrams and cross table and analyzed by contingency coefficient correlation test.The results obtained from the contingency coefficient correlation test (r = 0031 sig <Î± (0:05) so that Ho is rejected) there is health education on the prevention of diarrhea in infants with maternal attitudes in the prevention of diarrhea in children under five in health center Kandangan 2010The existence of such relationship in accordance Health education theories and KAP (knowledge-attitude-practice), in which health education can mepengaruhi knowledge, knowledge can influence the attitudes and behavior. With more and more often conducted health education about prevention of diarrhea, the better knowledge and determine a more positive attitude in the prevention of diarrhea. We can conclude the necessary health education in increasing knowledge and establish a positive attitude in the prevention of diarrhea.Â Â Key words: health education, attitudes, prevention of diarrhea